Comparison of Expressive Spoken Language Skills in Children With Cochlear Implants and Children With Typical Hearing - Socher, Michaela; Ellis, Rachel Jane; Wass, Malin; Lyxell, Björn (Frontiers in Psychology, 2020)
When children start formal education, they are expected to be able to express complex thoughts. However, in order to do so, they need to be able to use both complex grammatical structures and a variety of words. One group that is at risk of having a delay in terms of their expressive language ability is children with cochlear implants (CI). In this study, we evaluated whether children with CI perform comparably to children with typical hearing (TH) on a standard expressive grammar and a standard expressive vocabulary task when the groups were matched on non-verbal intelligence and working memory capacity. It was found that the children with CI in this study performed more poorly on a standard expressive vocabulary task, but not on a standard expressive grammar task when compared to the children with TH. Differences in terms of expressive vocabulary do not seem to be explained by differences in cognitive ability. In addition, the variation in terms of expressive language ability was larger in the children with CI compared to the children with TH. This might be explained by additional confounding factors, like the time of language deprivation or by a greater influence of cognitive differences for the acquisition of spoken language for children with CI. Furthermore, individual differences in terms of cognition do not seem to have a larger influence on the expressive language ability of children with CI compared to children with TH.